Edible leafy vegetables from West Africa (Guinea-Bissau): consumption, trade and food potential - Catarino, Luís (2019)
Wild Edible Plants are common in the diet of rural communities of sub-Saharan Africa. In Guinea-Bissau, West Africa, wild plant resources are widely used in human diet, but very few studies have addressed them. The aim of this study is to reveal: (1) the wild and semi-cultivated leafy vegetables consumed in Guinea-Bissau; and (2) the nutritional composition of those plants traded at the largest country market in Bissau. Our results revealed that 24 native or naturalized species with edible leaves are currently consumed by Guinea-Bissau population. Five of them were found at the market: dried leaves of Adansonia digitata, Bombax costatum and Sesamum radiatum, and fresh leaves and shoots of Amaranthus hybridus and Hibiscus sabdari a. The analysis of the nutritional properties revealed that leaves contain a significant amount of protein (10.1–21.0 g/100 g, dry basis), high values of macronutrients and micronutrients, as well as of phenolic compounds (13.1–40.3 mg GAE/g) and a considerable antioxidant capacity (DPPH 111.5–681.9 mg Eq Trolox). Although price and availability vary among the leafy vegetables analyzed, these traditional foods appear to be a good dietary component that can contribute to food security in Guinea-Bissau and in other West African countries, as these species are widely distributed in this region